Economic Growth: Can be Influenced by Exports, Inflation, and Government Expenditure on ASEAN-7 Countries during the AFTA Period? - Frans Simatupang; Marselina Marselina (Journal of Economics Research and Social Sciences, 2023)
The increase in the economy can be seen from the increase in export activities and government spending that have an impact on the increase in foreign exchange. The existence of inflation has an impact on the weakening of people's economic activities so that it has an impact on the weakening of the country's economy. However, inflation has a positive impact on a country's exports. The study analyzed the effect of exports, inflation and government expenditure on economic growth in ASEAN-7 countries from 2015 to 2019. Using Panel Data analysis method with RE model (Random Effect Model) as the best model used. The results of this study indicate a positive and significant relationship between exports and government expenditure on economic growth in ASEAN-7 countries, while inflation has a significant negative influence on economic growth in ASEAN-7 countries.